Meinungsbildung in Gruppen - Hegselmann, Rainer; Justus Liebig University Giessen (My University, 2009)
The article describes a radically simplifying model of opinion formation processes. The model abstracts away almost everything. A very common reaction to such an approach is the objection that important factors are not included. The article anticipates ten objections of this type and tries to show how to cope with them without giving up the radically simplifying approach. The strategies that we use can be summarized to a certain heuristics. Following the principles of this heuristics will often allow at least a partial qualitative understanding of real world phenomena. In many areas we probably cannot hope for more.
Keywords: ddc:100; ddc:330